Perlindungan Hukum Terhadap Konsumen PT. PLN (Persero) Dalam Pemanfaatan Jasa Listrik - Carissa Christiana (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2022)
Purpose writing this journal is as a requirement for graduation and get a law degree at the Faculty of Law, University of Surabaya. Practical purpose of this study was intended to determine the legal protection to consumers against PT. PLN (Persero) in the utilization or the use of electricity in terms of Law No. 8 Year 1999 Results of studies addressing that, PT. PLN has not given legal protection to consumers PT. PLN who have been harmed in the utilization of electrical services. PT. PLN in carrying out his duties as less electricity provider to provide information to consumers about their rights in the usage of electricity services so as to cause harm to consumers. In resolving disputes between PT. PLN to consumers can be resolved through the public courts or through the Consumer Dispute Settlement Body (BPSK) in accordance with the legislation (BFL). Legal protection of consumer electrical services such compensation has not been done by PT. PLN, given PT. PLN has done a power outage that caused a loss in consumer electrical services. The nest is dictated For consumers who are harmed can use peaceful means before using legal remedies through the judiciary as a last resort in resolving disputes. Keywords: Law Protection; Against Consumers; Electrical Services Utilization.